Studi Literatur Riset Akuntansi Dan Keuangan Masjid - Dwi Rizka Maulia; Ahmad Baehaqi (Jurnal Akuntansi dan Governance, 2021)
Managing resources originating from the congregation, mosques as non-profit religious organizations are encouraged to be transparent and accountable by implementing good accounting and financial management. Thus, a number of researches related to accounting and financial management of mosques have been conducted. This study uses descriptive analysis to review 102 national and international articles related to accounting and financial management of mosques published from 2010 to 2019. The result shows that the highest number of studies was conducted in 2018 and 2019 while Indonesia and Malaysia were the top two countries where the studies were conducted. Furthermore, the comparison between quantitative research and combined methods is still less than that of the qualitative approach. In addition, most research topics put their focus discussing about mosque management and accountability.